That's what we do! - Craig Paul (Scottish Journal of Residential Child Care, 2020)
For many children, some life experiences before Harmeny have not always been positive. Many have experienced significant early years trauma and we could not allow this pandemic to rock their foundation; too many bricks had been added to their secure base since they arrived. As I reflect on life at Harmeny since the impact of COVID-19 gripped the world, I could not be prouder of all our adults who have kept the service going around the clock. 'That’s what we do!' is a regular response, demonstrating their unconditional commitment. They have, like our colleagues in other residential services, given so much (professionally and personally) and the children will never forget it! I dedicate these memories to form part of our life story….